Smart Referencing: Strategi Efektif Pengelolaan Referensi untuk Mendukung Penulisan Karya Tulis Ilmiah Berkualitas pada Guru MGMP Sidoarjo (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
Limited competence among teachers in systematically managing scientific references remains one of the main challenges in producing high-quality scientific writing. This community service activity aims to enhance the competence of Biology MGMP teachers in Sidoarjo in reference management through a Smart Referencing approach using the Mendeley application as a Reference Management System. The methods employed include training sessions, hands-on practice, and mentoring in the use of Mendeley, covering installation, library management, and the automatic integration of citations and bibliographies into scientific documents. The evaluation of the activity was conducted through questionnaire distribution to measure participants’ improvement in understanding and skills. The analysis results indicate that several technical aspects, such as the use of the Mendeley plugin in Microsoft Word (score = 3.40) and the overall ease of use of the application (score = 3.00), fall into the high category on a maximum scale of 4. This suggests that although the application is perceived as useful, there is still a need for initial adaptation in its usage. Furthermore, the overall mean score of all questionnaire items is 3.74, with a satisfaction index of 93.5%, which falls into the very high category. These findings indicate that the Mendeley-based Smart Referencing training received very positive responses and was effective in improving participants’ understanding and skills in reference management for scientific writing.